Heavy Episodic Drinking and Its Consequences: The Protective Effects of Same-Sex, Residential Living-Learning Communities for Undergraduate Women - Boyd, Carol J. (2008)
Gender and living environment are two of the most consistent factors associated with heavy episodic drinking on college campuses. This study aimed to determine group differences in alcohol misuse and its attendant consequences between undergraduate women living in four distinct on-campus residential environments. A Web-based survey was self-administered to a stratified random sample of full-time students attending a large Midwestern University, and living in four distinct on-campus residential environments: 1) single-sex (all female) Residential Learning Communities (RLCs), 2) mixed-sex (male and female) RLCs, 3) single-sex (all female) non-RLCs and 4) mixed-sex (male and female) non-RLCs. Respondents living in single-sex and mixed-sex RLCs had significantly lower rates of alcohol use, heavy episodic drinking and related primary alcohol-related consequences when compared to respondents living in non-RLCs; however, women in single-sex RLCs had the lowest rates. RLCs – particularly single-sex learning communities – appear to provide undergraduate women with an environment that supports lower rates of alcohol use and abuse.